Role of herbs for elevating immunity against SARS-CoV-2: a concise review - Anand, Aashima; Saraswat, Juhi; Patel, Rajan (Faculty of Medicine, Universitas Trisakti, 2021)
COVID-19 has emerged as a dreadful pandemic caused by the virus SARS-CoV-2. Though the number of patients recovering from infection is encouraging, sturdy cure is still being researched upon and the effective vaccines are yet to be rigidly resolute. COVID-19 has so far instigated a massive loss of lives globally and even the countries with the most advanced healthcare systems have come under its grasp. Health experts suggest in such case â€œPrevention is better than cureâ€ which includes an appropriate daily lifestyle and a rugged immune system that could help mankind surmount this peril. This review highlights the importance of influential herbs and their medicinal significance. Biomedical articles were explored from PubMed, Google Scholar, Web of Science for the period of 2010-2021. Guidelines from the Ministry of Ayush (India) were also considered. The Ayurveda does not mention any cure for the novel coronavirus; however, it emphasizes the means of boosting oneâ€™s immunity. Accordingly, this article highlights some of the role of prevalent Ayurvedic herbs in promoting immunity for combating the novel coronavirus. The herbs in combination with drugs could be utilized for the sake of curtailing the side effects as well as the malefic repercussions of strong synthetic drugs used for treating COVID-19 patients, which would be a paramount leap in the field of Ayurveda as well as western-style medicine. However, the beneficial effects of these traditional medicines and their clinical trials remained to be known. We reviewed the latest updates on traditional medicines proposed for promoting immunity towards COVID-19.